(untitled) (Journal of Laboratory Animal Science, 2019)
Caesarean section (C-section) is conducted to decontaminate mice from microorganisms in our facility. In the present study, pregnant mice (C57BL/6J) were administered progesterone on gestational days (GD) 17 and 18 and were C-sectioned on GD 19 (normal schedule), 20 (1 day later than usual), or 21 (2 days later than usual). The fetal survival rates on GD 19 and 20 were similar, whereas on GD 21, it was quite low. In another set of study, pregnant mice (C57BL/6J) were administered progesterone on GD 17 and 18 (normal schedule), 16 and 17 (1 day earlier than usual), or 15 and 16 (2 days earlier than usual). The progesterone administration on GD 16 and 17 were as effective as the normal schedule in maintaining pregnancy until GD 19, whereas administering progesterone on GD 15 and 16 did not maintain pregnancy until GD 19. Administration of single shot of progesterone to pregnant (C57BL/6J) mice on GD 15, 16, 17, or 18 resulted in effective maintenance of pregnancy until GD 19 only in GD 18 group. These findings will allow us to better manage work schedules.